Building integrated photovoltaics powered electric vehicle charging with energy storage for residential building: Design, simulation, and assessment - Khan, Sanjay; Sudhakar, K.; Mohd Hazwan, Yusof (Elsevier Ltd, 2023)
Global warming poses a serious danger to the environment, animals, and the livelihoods of humans. The residential building sector & transportation sector has received significant attention in recent years due to GHG emissions. Electric vehicles (EVs) are poised to play an essential function in reducing dependency on non-renewable fuels and the transportation sector's environmental implications. On the other hand, the sustainability of EVs depends on their method of charging. This paper investigates the feasibility and design of a BIPV (building-integrated photovoltaic) powered EV charging system in a typical Malaysian house using solar energy to meet residential and EV charging demand. Three BIPV systems: Grid integrated with no battery, grid integrated with 75 % battery storage and grid integrated with 100 % battery storage have been designed, simulated, and assessed for the performance parameters. BIPV plant capacity of 5.6 kWp, roof inclination of 10°, and roof facing southeast and northwest have been sized for the proposed system. The annual energy output was 8.05MWh, 7.21MWh and 7.19MWh for the three scenarios. LCOE of the grid-connected system with no batteries showed the lowest value of 0.16RM/kwh, whereas a system with batteries had higher LCOE of 0.51RM/kWh and 0.65RM/kWh. The grid-connected system without batteries showed the highest GHG emission savings of 137,321,924 kgCO2e.